PENGARUH LEVERAGE TERHADAP KINERJA KEUANGAN PADA SUBSEKTOR LEMBAGA PEMBIAYAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Surna Lastri; Maidar Maidar; Muhajirin Muhajirin (STIE DWI SAKTI BATURAJA, 2018)
This study aims to determine the effect of leverage as measured by debt to equity ratio (DER) and debt to assets ratio (DAR) to financial performance as measured by return on assets (ROA), both individually (partially) and together (simultaneous ) This research is census research, which includes all sub-sector financing institutions listed on the Indonesia Stock Exchange that have met the criteria in the observation data. Observation period of research data from 2015 to 2017, totaling 15 companies. The analytical method used is linear multiple regression. The results of this study found that the debt to equity ratio and debt to assets ratio affect financial performance, both individually (partially) and together (simultaneously)